THE ΜΕΛΣΑ COINS IN THRACE (JOURNAL OF ANCIENT HISTORY AND ARCHAEOLOGY, 2021)
The present article deals with the short-term coinage with ΜΕΛΣΑ on its reverse that seems to have been issued in the fourth – beginning of third century BC. The author accepts that it is about an individual name and links it with the deeds of an unknown yet Thracian dynast in whose territory the Messambrian polichnion Bizone was established. At this very time a specific Messambrian coinage appeared revealing the creation of a new cult to the oikist whose name in the sources of 1st century BC is Melsas. The establishment of the polichnion in his territory and his potential support allowed this Thracian dynast to be honoured as an oikist whose cult received an impetus when the Dorian politeia joined the Thracian province of the Roman empire.